2013
DOI: 10.1007/s11136-013-0374-0
|View full text |Cite
|
Sign up to set email alerts
|

A mixed method exploration of survivorship among Chinese American and non-Hispanic White breast cancer survivors: the role of socioeconomic well-being

Abstract: Purpose Cancer-related stress is heavily influenced by culture. This study explored similarities and differences in survivorship care concerns among Chinese American and Non-Hispanic White (NHW) breast cancer survivors. Methods A sequential, mixed-method design (inductive/qualitative research-phase I and deductive/quantitative research-phase II) was employed. Eligible women identified from the Greater Bay Area Cancer Registry were age ≥21, diagnosed with stage 0-IIa breast cancer between 2006–2011, and had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 36 publications
(35 reference statements)
4
37
0
Order By: Relevance
“…A qualitative study reported that, low‐ to middle‐income Chinese immigrant survivors cannot afford cancer care services at convenient locations and were preoccupied with concerns for cancer care costs. Such difficulties brought negative impact on household duties, productivity at work, and family prosperity . Taken together, these findings from cancer populations suggest that education and income are interrelated but distinct SES resources and could be transformed into unique patterns of health impacts after cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A qualitative study reported that, low‐ to middle‐income Chinese immigrant survivors cannot afford cancer care services at convenient locations and were preoccupied with concerns for cancer care costs. Such difficulties brought negative impact on household duties, productivity at work, and family prosperity . Taken together, these findings from cancer populations suggest that education and income are interrelated but distinct SES resources and could be transformed into unique patterns of health impacts after cancer.…”
Section: Discussionmentioning
confidence: 99%
“…While the incidence rate of breast cancer has been declining among non‐Hispanic White people (NHWs), there is a dramatically rising trend among Asian Americans . Compared with NHWs, Asian American breast cancer survivors are largely underserved due to the status of being immigrants and cultural barriers in recruiting psychosocial resources, despite the increasing need for cancer care …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the survival of Asian patients with breast cancer is known to be longer than that of Caucasian women, probably owing more to lifestyle habits than to genetic susceptibility; however, this matter needs to be clarified by further studies. [37][38][39][40][41][42][43] Another issue concerns the best approach to define the optimal cut-off value for LNR, as median, quartiles and ROC curve analysis have been variably used by different authors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Asian American breast cancer survivors have reported lower QOL than their European counterparts [9, 10]; Chinese American survivors are more likely to experience poorer socioeconomic well-being than non-Hispanic White survivors [11]. Qualitative evidence has also shown that Chinese survivors describe more distress than Americans [12].…”
Section: Introductionmentioning
confidence: 99%